2019
DOI: 10.1101/724005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepC: Predicting chromatin interactions using megabase scaled deep neural networks and transfer learning

Abstract: Understanding 3D genome structure requires high throughput, genome-wide approaches. However, assays for all vs. all chromatin interaction mapping are expensive and time consuming, which severely restricts their usage for large-scale mutagenesis screens or for mapping the impact of sequence variants. Computational models sophisticated enough to grasp the determinants of chromatin folding provide a unique window into the functional determinants of 3D genome structure as well as the effects of genome variation. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…We also did not find much predictive gain in integrating local features from the two data sources, perhaps because local sequences were not informative enough for a higher prediction accuracy. We emphasize that, although our findings suggest that local DNA sequence data may not be sufficient to well predict EPIs, a new study has shown some promising results of using mega-base scale sequence data incorporating large-scale genomic context [39]; this is in agreement with improved prediction performance of including not only local epigenomic features of an enhancer and a promoter, but also the window region between them [40]. More studies are warranted.…”
Section: Discussionsupporting
confidence: 79%
“…We also did not find much predictive gain in integrating local features from the two data sources, perhaps because local sequences were not informative enough for a higher prediction accuracy. We emphasize that, although our findings suggest that local DNA sequence data may not be sufficient to well predict EPIs, a new study has shown some promising results of using mega-base scale sequence data incorporating large-scale genomic context [39]; this is in agreement with improved prediction performance of including not only local epigenomic features of an enhancer and a promoter, but also the window region between them [40]. More studies are warranted.…”
Section: Discussionsupporting
confidence: 79%
“…Variants within open chromatin were assessed for potential damage to transcription factor binding footprints using Sasquatch 20 (7-mer, WIMM Fibach Erythroid, Exhaustive). Variants within open chromatin were further classified based on their predicted effect on chromatin accessibility using a deep convolutional neural net 21 (deepHaem). Model architecture and data encoding were adapted from DeepSEA 36 with the following modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The platform addresses the fact that both causal and non-causal variants may lie in open chromatin. Using DNaseI footprinting and a machine learning approach the platform prioritises variants predicted to directly affect the binding of transcription factors or alter chromatin accessibility 20,21 . Having prioritised putative regulatory causal variants, the platform then links the regulatory elements in which they occur to genes using NG Capture-C, the highest resolution chromatin conformation capture (3C) method currently available for targeting numerous loci 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In Schwessinger et al 30 , the authors report successful predictions of Hi-C maps at 10kb resolution using a similar deep convolutional neural network approach, deepC. While deepC has a similar 'trunk' to Akita, it differs greatly in the architecture of the 'head', data preprocessing, and training schemes.…”
Section: Supplemental Note 2: Differences With Deepcmentioning
confidence: 99%
“…The architectures and layers that might best reflect the process of loop extrusion, believed to organize mammalian interphase chromosomes, 29 or other mechanisms of genome organization remain open questions. The near future promises exciting progress: recently, a similar CNN model, deepC, was posted to bioRxiv 30 . While deepC has a similar 'trunk' to Akita, it differs greatly in the architecture of the 'head', data pre-processing, and training schemes (Supplemental Note 2).…”
mentioning
confidence: 99%